APLIKASI METODE CROSTA UNTUK PENENTUAN ZONA UBAHAN DI DAERAH KAMPUS LAPANGAN CISOLOK, SUKABUMI DAN SEKITARNYA - Arif Budiyono (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2019)
Crosta method is a method of remote sensing data processing to determine alteration zones associated with mineralization in an area with favorable geological conditions. The Crosta method is applied to remote sensing image data in the Cisolok field campus area, Sukabumi. The enhancement process of the 1,3,4,5 and 1,4,5,7 bands gives a picture of the significant zone separation between the distribution of clay changes and the distribution of iron oxide changes in the study area. Data validation was carried out on the determined observation points and gave an average Fe 2O3 content of 15.2%. The geological structure and various alteration zones in the Cisolok field campus area, Sukabumi provide significant added value in the application of this method in separating zones of iron oxide and clay alteration.